Structural equation modeling of self-esteem, motives of participating in physical activity and duration of physical activity among adolescents in Kota Bharu, Kelantan - Ab.Lah, Nurzulaikha Mahd (2016)
Introduction: Physical activity (PA) is an important daily routine that can maintain our health, whereas engaging in sedentary lifestyle can cause lifestyle-related diseases. There is no age limit of being active, but it is important to start from early age. Motivation of participating in PA is important to motivate people to sustain their PA regularly. Selfesteem could be a trigger factor to motivate people to increase the duration of PA. This study attempted to uncover how much self-esteem, motives of participating in any PA, and the duration of PA are related among adolescents, specifically in secondary school students in Kota Bharu, Kelantan. Objective: The study aimed to assess the level of self-esteem and motives of participating in PA and to ensure that both constructs are reliable and valid measures. Then, the inter-relationships between self-esteem, motives of participating in PA and duration of PA were examined using structural equation modeling (SEM). Method: A cross-sectional study was conducted among secondary schools‟ students in Kota Bharu, Kelantan using self-administered questionnaire. Participants were selected using cluster sampling method. Three schools were randomly selected from a total of 48 schools in Kota Bharu, Kelantan. The classes that involved in the study, within the selected schools were determined by the schools‟ principal. Self-esteem was measured using State Self-esteem Scale (SSES) and motives of participating in PA were measured using Physical Activity Leisure Motivation Scale (PALMS-Y). The scales were translated into Malay language using the standard procedure and there were named as SSES-M and PALMS-Y-M. Descriptive, confirmatory factor analysis (CFA), and SEM were used in statistical analysis. Results: Participants were 783 secondary school students (female= 57.3%, male= 42.7%) from Kota Bharu, Kelantan. Majority of the students were Malay (57.3%). Overall, theaverage of self-esteem and motives of participating in PA were 2.92 (SD=0.64) and 3.75 (SD=0.71) respectively. For measurement model assessment, SSES-M scale showed good fit to the data after some improvement were made (CFI=0.966, TLI=0.949, SRMR=0.030, RMSEA=0.040 (0.026, 0.055), Clfit p-value=0.861) with nine items remained. For PALMS-Y-M, the majority of the fit indices were within the acceptable threshold values (CFI=0.928, TLI=0.917, SRMR=0.048, RMSEA= 0.045 (0.042, 0.049), Clfit p-value= 0.982) with all items remained. The composite reliability for SSES-M and PALMS-Y-M were ranged from 0.582-0.632 and 0.622-0.823 respectively. Overall, the final SEM model showed a good fit to the data based on several fit indices (CFI=0.919, TLI=0.908, SRMR=0.048, RMSEA=0.044 (0.040, 0.047), Clfit p-value=0.998) with five hypotheses supported. The final SEM model explained 25% of the total variance in duration of PA, which was statistically significant. Conclusion: The SEM model tested in the present study provided useful insight in regard to the direct and indirect relationships among the study variables. The finding from the present study could provide valuable information that could help the teachers, health educators, health policy makers, and parents in promoting exercise and physical activity among secondary school students.